Indonesia higher education’s online learning during the pandemic state - Elisabeth Rukmini; Hanna Angelina; Viktoria Cosinta Anggreni (Institute of Advanced Engineering and Science, 2023)
The COVID-19 pandemic has brought significant changes in Indonesian higher education to switch the learning activities to online learning. During the online learning implementations, researchers tried to record the changes and discussed the problems they faced. This systematic review aimed to summarize the growth of online learning for Indonesian higher education during the COVID-19 and to describe the connection between trends of online learning’s growth and stakeholders’ interests. Ultimately, this systematic review wanted to forecast the scenario after seeing the overall progress of online learning in higher education institutions in Indonesia. The authors conducted a systematic literature review using PRISMA protocol and collected articles from Google Scholar, EBSCOHost, SAGE, Taylor & Francis, and Proquest. A total of 1,206 studies were retrieved from all databases. The authors excluded some articles that did not come originally from Indonesia, did not involve participants from universities, and were not empirical research. A final eighty-six articles were collected for analysis. The results revealed that infrastructure, interactivity, and readiness were the three main discussions for all Indonesian higher education stakeholders. The authors provided four scenarios for online learning in Indonesia, and the Cyber Growth scenario was the preferred scenario for higher education in Indonesia.